Kompetencje nauczycieli edukacji medialnej - Strykowski, Wacław; Kąkolewicz, Mariusz; Ubermanowicz, Stanisław (Wydawnictwo Naukowe UAM Poznań, 2008)
The media education is a new field of teaching in Polish schools. The main problems in introducing the new subject, especially if it is so interdisciplinary and delivered across the curriculum of other school subjects, is how to prepare teachers and what competencies they should have. In the article, the authors deal with the last problem and consider it from two different perspectives. One is analytical and comes out from more traditional division of media and communications channels, the other can be described as holistic. So two, analytical and holistic, lists of media teacher competencies were formulated and they are preceded by the short analysis of new trends in information technologies and general goals of media education.
Competencies of media education teachers